Coronary Stent Placement in an Interarterial Anomalous Right Coronary Artery: An Alternative Approach in a Multimorbid High-risk Surgical Patient - Erik J Simon; Mary Rodriguez Ziccardi; Saagar Sanghvi; Amer K Ardati (Interventional Cardiology: Reviews, Research, Resources)
Anomalous aortic origin of a coronary artery is a rare congenital anomaly and potential aetiology for sudden cardiac death. However, the mere presence of this anomaly does not portend clinical significance, and there are many factors that contribute to limiting coronary blood flow in these patients. The standard of care for symptomatic individuals is surgical management with coronary unroofing although not all cases are amenable to surgery. We report the case of an anomalous right coronary artery with interarterial course managed by percutaneous coronary intervention due to surgical contraindication secondary to comorbidities. The proposed mechanism of action culminating in aborted sudden cardiac death is unique and involves aggravated pulmonary hypertension in an individual with severe comorbid pulmonary disease.